Work, family, and faith : rural southern women in the twentieth century - Walker, Melissa, 1962-; Sharpless, Rebecca (University of Missouri Press, 2006)
"Collection of essays capturing the transformation of the American South from agrarian to industrial/commercial over the course of the twentieth century from the perspective of women struggling against poverty by relying on tradition and inner strength"--Provided by publisher